Psychosis susceptibility zinc finger protein 804A (ZNF804A) gene polymorphism in schizophrenia patients treated with olanzapine in North Indian population. (4th May 2023) - Maity, Sayantika; Munisamy, Murali; Sagar, Rajesh; Udupa, Nayanabhirama; Puluturu Shilpa, Venkata; Subbiah, Vivekanandhan
Abstract: Purpose: The Zinc finger protein 804A (ZNF804A) is a potential schizophrenia candidate gene that has emerged from genome-wide association studies. The aim of the study is to investigate whether this gene variant influences the response of positive or negative symptoms to antipsychotic drug olanzapine in North Indian schizophrenia patients. Materials and methods: Our study involved 184 unrelated schizophrenia cases (114 males and 70 females; mean age: 52.8 ± 11.6 years) and 300 normal controls (168 males and 132 females; mean age: 54.9 ± 6.9 years). At the start of treatment and after four weeks, we assessed the response of positive and negative symptoms by positive and negative syndrome scale (PANSS). Olanzapine drug level was estimated using HPLC Method and Genotyping was performed using PCR-Snap Shot technique. Results: Significant differences were observed in the genotype distribution ( χ 2  = 6.10, d.f. = 2, p  = 0.04) and allele frequencies ( χ 2  = 5.14, d.f. = 1, p  = 0.02; odds ratio = 0.57, 95% confidence interval =1.09–3.48) between schizophrenia patients and controls group. The improvement of positive and negative schizophrenia symptoms after 4 weeks of treatment with olanzapine was assessed. Patients homozygous for the ZNF804A risk allele for AA show poorer improvement of positive symptoms compared to patients with a protective allele. Conclusions: Our findings indicate that ZNF804A gene polymorphism plays a significant role in the treatment of schizophrenia, suggesting that ZNF804A may be an effective marker for schizophrenia treatment.